Automata Theory in Computing Education: A Systematic Review - Silva, Júlia Veiga da; Cavalheiro, Simone André da Costa; Foss, Luciana (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2024)
This paper presents a systematic literature review investigating approaches to teaching Automata Theory in Computing Education. Automata Theory, a foundational area of Computer Science essential for understanding formal languages and compilers, is increasingly recognized for its importance in educational contexts. This study examines how Automata Theory is approached, assessed, integrated, and taught in both higher education and K-12 settings. The review reveals several innovative and traditional methods used to enhance student engagement and comprehension, including educational tools and games. However, the findings highlight a lack of standardized assessment methods in current practices, as well as a gap in approaches in the K-12 context.